A spatiotemporal atlas of mouse gastrulation and early organogenesis to explore axial patterning and project in vitro models onto in vivo space - Luke T.G. Harland; Tim Lohoff; Noushin Koulena; Nico Pierson; Constantin Pape; Farhan Ameen; Jonathan Griffiths; Bart Theeuwes; Nicola K. Wilson; Anna Kreshuk; Wolf Reik; Jennifer Nichols; et al. (Cell Reports, 2025)
Summary: During gastrulation, mouse epiblast cells form the three germ layers that establish the body plan and initiate organogenesis. While single-cell atlases have advanced our understanding of lineage diversification, spatial aspects of differentiation remain poorly defined. Here, we applied spatial transcriptomics to mouse embryos at embryonic (E) E7.25 and E7.5 days and integrated these data with existing E8.5 spatial and E6.5–E9.5 single-cell RNA-seq atlases. This resulted in a spatiotemporal atlas of over 150,000 cells with 82 refined cell-type annotations. The resource enables exploration of gene expression dynamics across anterior-posterior and dorsal-ventral axes, uncovering spatial logic guiding mesodermal fate decisions in the primitive streak. We also developed a computational pipeline to project additional single-cell datasets into this framework for comparative analysis. Freely accessible through an interactive web portal, this atlas offers a valuable tool for the developmental and stem cell biology communities to investigate mouse embryogenesis in a spatial and temporal context.